6. ALS disability is predicted by a shift in the balance between short latency facilitatory and inhibitory circuits. Issue 4 (April 2018) - van den Bos, Mehdi A.J.; Menon, Parvathi; Geevasinga, Nimeshan; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objectives: Cellular work in TDP-43 models of ALS highlight a key role for somatostatin interneuronal circuits in mediating corticomotoneuronal hyperexcitability. Previous studies in ALS patients disclosed a reduction of short interval intracortical inhibition (SICI), a biomarker of interneuronal inhibitory function. Threshold tracking transcranial magnetic stimulation (TMS) provides a non-invasive method for assessing cortical interneuronal function in the human motor cortex. Short interval intracortical facilitation (SICF) is a novel biomarker for assessing the function of excitatory cortical interneuronal circuits. The present study assessed SICI and SICF in a cohort of sporadic ALS patients to further dissect the relative contribution of excitatory and inhibitory cortical circuits in development of cortical hyperexcitability in ALS. Methods: Threshold tracking TMS was used to assess motor cortical function in 25 ALS patients, with results compared to 19 healthy older controls. SICF was measured by setting the subthreshold conditioning stimulus to 95% of resting motor threshold with interstimulus intervals (ISI) between 1 and 5 ms. A concurrent measure of SICI was also made. We developed a novel "Index of Excitation" which quantified the relative contribution of inhibitory (SICI) and facilitatory (SICF) circuits in development of cortical hyperexcitability. Results: Mean SICF was significantly increased in ALS patients (ALS = −18.15 ± 1.80%; controls = −8.49 ± 1.59%%, P < 0.001). This increase in SICF was accompanied by a significant reduction in SICI (ALS = 3.89 ± 1.54%, controls = 15.26 ± 1.48%, P < 0.001). Importantly, the Index of Excitation was significantly increased in ALS patients (mean ALS = 83.84 ± 7.57%; controls = 33.74 ± 4.33%, P < 0.001), suggesting that increased activity of facilitatory circuits contributed to the development of cortical hyperexcitability. Interestingly, there was a significant correlation between the Index of Excitatation and the ALSFRS-R (R 2 = 0.27, P < 0.001), i.e. patients with greater hyperexcitability exhibited more clinical disability. A trend towards predicting upper motor neuron dysfunction was present (R 2 = 0.20, P = 0.055). Conclusion: This study has established that cortical hyperexcitability in ALS is mediated through a combination of reduced inhibition (implying dysfunction of inhibitory circuits) and increased activity of facilitatory cortical networks. The Index of Excitability, a novel measure of corticomotoneuronal hyperexcitability, appears to predict the clinical burden of disease in ALS patients, displaying potential as a therapeutic biomarker. Strategies aimed at modulating the imbalance in cortical inhibition and excitation may prove therapeutically useful.